Analisis Semiotika dan Representasi Emotional Healing dalam Lagu “Perayaan Mati Rasa” Karya Umay Shahab Ft. Natania Karin - Fadia Rachma Putri; Agustina Kusuma Dewi (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2026)
The phenomenon of emotional healing has become increasingly prominent in popular culture as the younger generation experiences increasing loss, emotional exhaustion, and numbness. Popular music serves as a medium of expression, representing these emotional dynamics through poetic language and symbolic structures. This study aims to analyze the emotional representation of healing in Umay Shahab's song "Perayaan Mati Rasa" using Roland Barthes's semiotic approach. The research method used is descriptive qualitative, analyzing three layers of meaning: denotation, connotation, and myth, through breaking down the lyrics into several lexicons and reading signs. The results show that (1) denotatively, the lyrics construct an emotional arc from inner tension to self-contemplation; (2) connotatively, the use of diction and imagery represents vulnerability, resilience, and emotional reflection; and (3) at the mythical level, the song constructs release as a form of emotional maturity and loss as a process of identity formation. Thus, this song functions as a cultural representation in interpreting the process of emotional healing in popular culture.